Incidence of Aberrative Lipids in Patients with Coronary Artery Disease - Iqtidar Ud Din, Tanveer Ahmad, Imran Khan, Yasir Arafat, Sajjad Ullah Khan, Muhammad Abdul Rauf (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to assess the prevalence of lipid abnormalities in patients presenting with coronary artery disease. Study Design: Cross-sectional Place and Duration: In the Cardiology department of Qazi Hussain Ahmad Medical Complex hospital, Nowshera for six-months duration from February 2021 to January 2022. Methodology: 175 patients of both genders with ages 20-80 years were included in this analysis. Following informed consent, patients’ vital statistics, including age, sex and BMI were recorded. Each patient had a blood sample obtained to analyze in the lab. Cholesterol, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) were all monitored on a regular basis. The entire dataset was examined via SPSS 22.0. Results: We found that majority of the patients were males 112 (64%) were males and females were 63 (36%). Majority of the patients 65 (37.1%) had age >60years and 95 (54.3%) had BMI >25kg/m2. Among 175 patients, we found abnormal lipid profile found in 82 (46.9%) cases. Among cases of abnormal lipid profile, cholesterol 203.17±6.44 and LDL was found higher 108.6±13.45, while HDL-Cholesterol was lowered 51.64±7.25. We found that serum triglycerides were also higher 212.19±28.49 among cases of abnormal lipid profile. Conclusion: In this study, we found that total cholesterol and LDL were considerably higher than HDL c in patients who presented with coronary artery disease, and that the frequency of lipid profiles was high. Keywords: Serum triglyceride, Coronary Artery, Lipid profile, Serum cholesterol,